TINJAUAN YURIDIS KETERLIBATAN TENTARA NASIONAL INDONESIA DALAM PENANGGULANGAN TINDAK PIDANA TERORISME DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 34 TAHUN 2004 TENTANG TENTARA NASIONAL INDONESIA - Ricky Nainggolan; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Terrorism is a crime that has been classified as extraordinary crime, or extraordinary crime. It is no stranger to the world because of the ongoing series of terrorism incidents. In Law Number 34 Year 2004 the issue of terrorism is the responsibility of the Indonesian Armed Forces (TNI), with the Terror Countermeasures Unit (Sat-Gultor 81) in it, the role of dealing with the problem of terrorism if needed. Terrorism is the most distressing crime of the world community, because it can happen anytime, anywhere, and sacrifice anyone. Has been taking the world's attention especially in the last few decades. The fact that this terrorism event can not be stopped by any party, even a country with high security though still exposed to terrorism attacks.The purpose of this research is to know how the steps of authorized institutions through the involvement of the Indonesian National Army (TNI) and the Police of the Republic of Indonesia (POLRI) in tackling terrorism in Indonesia, as well as the achievement of results by the authorized institutions. Based on the analysis conducted with literature review, and by using descriptive research method, it can be seen that there are measures of countermeasures terrorism conducted by the authorized institutions, namely in the form of prevention and action. If the POLRI measures in tackling terrorism network in Indonesia through prevention covering socialization or anti terrorism campaign and action in the form of arrest and stipulation of punishment in accordance with provisions of applicable law.Prevention and action is not enough to solve the problem of terrorism in Indonesia. Because the constitution that places terrorism crimes as a criminal offense of order and security disturbance, so the problem of terrorism is only a matter of law whereas terrorism is an armed resistance that endangers the safety of the nation and the sovereignty of the state.Keywords: International Terrorism, TNI, Prevention and Action